Tectorigenin protects against experimental fulminant hepatic failure by regulating the TLR4/mitogen‐activated protein kinase and TLR4/nuclear factor‐κB pathways and autophagy. (30th January 2019) - Zhang, Lingjian; Zhao, Yalei; Fan, Linxiao; Xu, Kai; Ji, Feiyang; Xie, Zhongyang; Ouyang, Xiaoxi; Wu, Daxian; Li, Lanjuan
Abstract : Tectorigenin has received attention due to its antiproliferation, anti‐inflammatory, and antioxidant activities. In this study, we investigated the effects of tectorigenin on lipopolysaccharide (LPS)/D‐galactosamine(D‐GalN)‐induced fulminant hepatic failure (FHF) in mice and LPS‐stimulated macrophages (RAW 264.7 cells). Pretreatment with tectorigenin significantly reduced the serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), histological injury, apoptosis, and the mortality of FHF mice, by suppressing the production of inflammatory cytokines such as TNF‐α and IL‐6. Tectorigenin also suppressed the activation of the inflammatory response in LPS‐stimulated RAW 264.7 cells. Tectorigenin‐induced protection is mediated through its mitigation of TLR4 expression, inhibition of mitogen‐activated protein kinase (MAPK) and nuclear factor‐κB (NF‐κB) pathway activation, and promotion of autophagy in FHF mice and LPS‐stimulated RAW 264.7 cells. Therefore, tectorigenin has therapeutic potential for FHF in mice via the regulation of TLR4/MAPK and TLR4/NF‐κB pathways and autophagy.